GOLD SOLUBILITY IN COMPLEX SULFIDE-CHLORIDE FLUIDS AT 300-500°C AND PTOTAL = 1 KBAR - Likhoidov G.G.; Nekrasov I.Ya. (My University, 2001)
Gold solubility was studied by the ampoule-autoclave method in relation to the NaCl concentration in fluid on isopleths of 0, 1, 3, 5m at oxygen and sulfur fugacities buffered by HMP and PPM mineral mixtures. Gold concentrations in quenched solutions (log m Au range) from -4.25 to -7.60. The results allowed us to describe the dependence between logm Au and T on mNaCl isopleths by equation logm Au = aT + b. Coefficients in this equation were calculated, and the surfaces of Au solubility in the logm Au-mNaCl-T space were plotted for each buffer. The relative locations of these surfaces provide evidence for the control of the bulk Au solubility in the studied part of the system by the interaction of chloride and sulfide components, which excludes simple additivity. An increase of the NaCl concentration in the fluid can either increase or decrease the Au solubility depending on the buffer composition. The participation of Au chloride complexes in the bulk solubility of this element is registered with confidence only at mNaCl higher than about 0.5 and is most typical of environments buffered by PPM.